Trifluoromethyl-phenyl-triazolyl derivative of beta-bisabolol induces cell death in ME-180 cervical cancer cells through induction of apoptosis and ROS generation (Bangladesh Journal of Pharmacology, 2015)
The aim of the current investigation was to design, synthesize and demonstrate the anticancer and apoptotic activity of trifluoromethyl-phenyl-triazolyl derivative of beta-bisabolol (TTB) in ME-180 human cervical cancer cells.  MTT and clonogenic assays were used to evaluate the cell viability and colony formation tendencies of the cells respectively. Phase contrast and fluorescence microscopic investigations were used to evaluate the effect of TTB on cellular morphology and apoptosis. Flow cytometric analysis using fluorescent CM-DCFH2-DA were used to study the effect of TTB on reactive oxygen species (ROS) formation. The results revealed that TTB significantly inhibited the proliferation of ME-180 human cervical cancer cells in a time-dependent as well as dose-dependent manner. TTB has the capacity to inhibit both anchorage dependent as well as anchorage independent growth of ME-180 cervical cancer cells. TTB-treated cells revealed chromatin condensation, fragmented nuclei and nuclear shrinkage. A 3-fold increase of ROS production was seen after 72 ?M TTB treatment.Video Clip of Methodology:Phase contrast microscopic study:  2 min   Full Screen   Alternate